Measurement of electrons from semileptonic heavy-flavor hadron decays in pp collisions at √s=7 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Masoodi, A. Ahmad; Ahmad, N.; et al. (AMER PHYSICAL SOC, 2012)
The differential production cross section of electrons from semileptonic heavy-flavor hadron decays has been measured at midrapidity (\y\ < 0.5) in proton-proton collisions at root s = 7 TeV with ALICE at the LHC. Electrons were measured in the transverse momentum range 0.5 < p(t) < 8 GeV/c. Predictions from a fixed-order perturbative QCD calculation with next-to-leading-log resummation agree with the data within the theoretical and experimental uncertainties. DOI: 10.1103/PhysRevD.86.112007
Keywords: PROTON-PROTON COLLISIONS; PROMPT PHOTON PRODUCTION; HIGH TRANSVERSE-MOMENTUM; QUARK-GLUON PLASMA; P(P)OVER-BAR COLLISIONS; J/PSI PRODUCTION; CROSS-SECTIONS; ALICE; PROTOTYPES; XE; Astronomy & Astrophysics; Physics